Modeling and simulation of a silicon soil moisture sensor based on the DPHP method for agriculture - Valente, A. (2003)
A silicon soil moisture sensor, based in the dual-probe heat-pulse (DPHP) method, was modeled and simulated for achieving, with low cost, accurate and reliable measurements. This method is based on the application of a heat pulse during a fixed interval of time. The maximum rise in temperature (∆Tm) is monitored by the measurement probe, placed at a certain distance of the heater source. A lowcost high-performance and small temperature sensor (a dynamic VPTAT generator) is required to be placed into the probe which have 0.912 mm in diameter and 20 mm long. If one considers the range of water contents, ratio of water mass to dry soil mass, in a typical agricultural soil (0.05 to 0.35m3 m¡3), the average sensitivity of the dual probe is about 1:95ºC per unit change (m3m-3 in water content forq = 400 Jm-1.